FACEBOOK USAGE TOWARDS READING INTEREST AT NEWS PORTAL MERDEKA.COM IN NORTH CIKARANG - Dindin Dimyati; Juvenia Juvenia (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2017)
Popularity of social media have grown since the early of 2000. They have eased people in exchanging information and sustaining relationship. In addition, social media have become an alternative for news distribution and consumption. One of popular social media platforms is Facebook in which many media organizations have utilized it as a medium for sharing information including news to provide up-to-date information, to increase article views, as well as to increase website traffics to visit their news portals. This research attempted to investigate the influence of Facebook usage towards reading interest at news portal merdeka.com, a study in North Cikarang. Theory used in this study wasUses and Gratification and the method was quantitative in nature. The data were collected through questionnaires for 100 respondents and SPSS 20 was employed to process the data. The result has shown that Facebook usage influenced 30.6% towards reading interest at news portal merdeka.com and the regression coefficient values obtained in this study was Y= 5.489 + 0.575X. In short, Facebook as a publication medium used by merdeka.com has successfullyincreasedreading interest to its news portal.